2011
DOI: 10.1007/s00265-011-1260-9
|View full text |Cite
|
Sign up to set email alerts
|

Information content of female copulation calls in wild long-tailed macaques (Macaca fascicularis)

Abstract: Primates are unusual in that many females display sexual signals, such as sex skin swellings/colorations and copulation calls, without any sex role reversal. The adaptive function of these signals remains largely unclear, although it has been suggested that they provide males with information on female reproductive status. For sex skin swellings, there is increasing evidence that they represent a graded signal indicating the probability of ovulation. Data on the functional significance of copulation calls are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 64 publications
1
23
2
Order By: Relevance
“…Moreover, it must be remembered when considering our results that we did not have data on female/male leaves and Hinde's index [Hinde and Atkinson, 1970], and an analysis of such detailed data [see Van Belle et al, 2009] may have found which member of each male-female dyad was responsible for maintaining close proximity. We also found that females uttered more copulation calls during the fertile phase, which contrasts with previous studies of other species [long-tailed macaques: Engelhardt et al, 2004Engelhardt et al, , 2012Barbary macaques: Pfefferle et al, 2011]. Together with recent results from crested macaques [Higham et al, 2012], our data are among the first to find a relationship between increased copulation call expression and the timing of ovulation.…”
Section: The Role Of Female Sexual Signals In Indicating the Fertile contrasting
confidence: 85%
See 2 more Smart Citations
“…Moreover, it must be remembered when considering our results that we did not have data on female/male leaves and Hinde's index [Hinde and Atkinson, 1970], and an analysis of such detailed data [see Van Belle et al, 2009] may have found which member of each male-female dyad was responsible for maintaining close proximity. We also found that females uttered more copulation calls during the fertile phase, which contrasts with previous studies of other species [long-tailed macaques: Engelhardt et al, 2004Engelhardt et al, , 2012Barbary macaques: Pfefferle et al, 2011]. Together with recent results from crested macaques [Higham et al, 2012], our data are among the first to find a relationship between increased copulation call expression and the timing of ovulation.…”
Section: The Role Of Female Sexual Signals In Indicating the Fertile contrasting
confidence: 85%
“…These signals seem to be related to sexual hormones such as estrogen and progesterone levels though studies in several species have found that they do not accurately indicate the timing of ovulation [e.g., longtailed macaques: Engelhardt et al, 2004;Barbary macaques: Pfefferle et al, 2008], with the exception of a recent study on crested macaques [Higham et al, 2012] that reopens the question about the role of copulation calls in ovulatory signaling. Copulation calls provide information on female identities [Semple, 2001;Townsend et al, 2011] which could influence female mating success Pfefferle et al, 2008] or decrease the capacity for male monopolization [Engelhardt et al, 2012;Townsend et al, 2011]. Maestripieri and Roney [2005] suggested that copulation calls in baboons may aid postcopulatory female choice by enhancing sperm competition or promoting mate guarding, but as with olfactory cues and sex skin signals, their role in multimodal sexual signaling remains unclear for most species.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…At the same time, primate signals in the auditory modality are also well described. Well-studied vocal signals include food calls (e.g., rhesus macaques Hauser 1992), the alarm calls of species such as vervet monkeys (Seyfarth et al 1980) and Diana monkeys (Zuberbühler et al 1997), but also signals that are almost certainly related to sexual selection, such as male loud calls (e.g., gelada, Gustison et al 2012; crested macaques, Neumann et al 2010) and copulation calls, which may occur in both females (e.g., Barbary macaques, Pfefferle et al 2008a, b; Semple and McComb 2000; long-tailed macaques, Engelhardt et al 2012; yellow baboons, Semple et al 2002) and males (rhesus macaques, Hauser 1993; Manson 1996). Although olfactory signals are less well studied (Heymann 2006a), there is increasing evidence that they play a significant role not just in strepsirrhines such as lemurs (Boulet et al 2009; Charpentier et al 2010), but also in platyrrhines (Ziegler et al 1993; Heymann 2006b) and even catarrhines (e.g., mandrills, Setchell et al 2011; chacma baboons, Clarke et al 2009; stump-tailed macaques, Cerda-Molina et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These caveats aside, multi-level models have achieved greater prominence in recent years [Janson, 2012], and an increasing number of primatological studies now use them [to give just a few examples: obeservational data Clarke et al, 2009;Gomes et al, 2009;Engelhardt et al, 2012;Koyama et al, 2012;Henzi et al, 2013, experimental field data: Wheeler, 2010Ducheminsky et al, 2014;Price & Fischer, 2014], not least because they are an ideal way to combat potential problems of pseudoreplication. Waller et al [2013] explicitly recommend the use of multi-level models (GLMM) as a way to combat pseudoreplication in experimental studies of primate communication.…”
Section: A Potential Solution: Multi-level Modelingmentioning
confidence: 99%